Decision support system design based building roof and structure selection for building contractors - Ghazizahedi, Mahziyar; Khalily Dermany, Mohmmad (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The contractors must consider the structure ability to cope and resist against accidental phenomena such as earthquake, flood, storm or fire, during the structure service life. In this way, the major losses of life and property are prevented as far as possible. In this regard, the building roof and structure selection is of great importance among contractors. The main objective of this research is to provide a model for building contractors for building roof and structure selection using the decision support system. Accordingly, a decision support system is designed for building contractors to select the building roof and structure using analytical Hierarchy process (AHP) and VIKOR techniques. The data were collected using a questionnaire.